Cyclophilin D Modulates the Cardiac Mitochondrial Target of Isoflurane, Sevoflurane, and Desflurane. Issue 5 (May 2017) - Harisseh, Rania; Chiari, Pascal; Villedieu, Camille; Sueur, Pauline; Abrial, Maryline; Fellahi, Jean-Luc; Ovize, Michel; Gharib, Abdallah
Abstract : Background: Volatile anesthetics are known to limit myocardial ischemia–reperfusion injuries. Mitochondria were shown to be major contributors to cardioprotection. Cyclophilin D (CypD) is one of the main regulators of mitochondria-induced cell death. We compared the effect of isoflurane, sevoflurane, and desflurane in the presence or absence of CypD, to clarify its role in the mechanism of cardioprotection induced by these anesthetics. Methods: Oxidative phosphorylation, mitochondrial membrane potential, and H2 O2 production were measured in isolated mitochondria from wild-type (WT) or CypD knockout mice in basal conditions and after hypoxia–reoxygenation in the presence or absence of volatile anesthetics. Results: All volatile anesthetics inhibited mitochondrial state 3 of complex I, decreased membrane potential, and increased adenosine diphosphate consumption duration in both WT and CypD knockout mice. However, they differently modified H2 O2 production after stimulation by succinate: CypD ablation reduced H2 O2 production, isoflurane decreased H2 O2 level in WT but not in CypD knockout mice, sevoflurane affected both lines whereas desflurane increased H2 O2 production in CypD knockout and had no effect on WT mice. Conclusions: This study showed different effects of isoflurane, sevoflurane, and desflurane on mitochondrial functions and highlighted the implication of CypD in the regulation of adenosine diphosphate consumption and complex I–induced radical oxygen species production.